2016
DOI: 10.1118/1.4949000
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Varian TrueBeam electron phase–spaces for Monte Carlo simulation of MLC‐shaped fields

Abstract: TrueBeam electron phase-spaces available from Varian have been implemented in two distinct Monte Carlo simulation packages to produce dose distributions and outputs that largely reflect measurement. Differences exist in the profile shoulders and penumbra tails for the 20 MeV phase-space off-axis and in the outputs for the 6 MeV phase-space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…29,30,50 Gamma pass rates of 2%/2 mm and 3%/3 mm have been reported for pMLC-shaped beams with high-and low-energy beams respectively. 33,34 In our study, Monte Carlo calculations agreed with measurements satisfying gamma criterion of 1%/1 mm for PDD calculations and 2%/ 1 mm for profiles. However, we were only able to achieve FWHM and penumbra within 0.4 cm of the measurements.…”
Section: B Monte Carlo Model Validationsupporting
confidence: 81%
See 2 more Smart Citations
“…29,30,50 Gamma pass rates of 2%/2 mm and 3%/3 mm have been reported for pMLC-shaped beams with high-and low-energy beams respectively. 33,34 In our study, Monte Carlo calculations agreed with measurements satisfying gamma criterion of 1%/1 mm for PDD calculations and 2%/ 1 mm for profiles. However, we were only able to achieve FWHM and penumbra within 0.4 cm of the measurements.…”
Section: B Monte Carlo Model Validationsupporting
confidence: 81%
“…Monte Carlo simulations have been used to demonstrate the feasibility and to further advance the use of existing photon MLC for electron collimation to produce clinically acceptable dose distributions. 1,5,9,20,[30][31][32][33][34][35][36][37] In a more recent study, Mueller et al have performed a comprehensive study of pMLC collimated electron beams including MC simulations of patient cases. 38 It was concluded that treatment plans using cut-outs can be replaced by plans of similar quality using pMLC collimation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues were addressed in recent studies by demonstrating the viability of delivering modulated electron radiation therapy (MERT) with a photon multileaf collimator (MLC) to eliminate the accessory requirements (applicators, cut‐outs, electron‐specific MLC) of traditional electron RT . By delivering MERT plans with a standard photon MLC, the potential arises for seamless mixed electron–photon delivery without interrupting treatment delivery between modality changes.…”
Section: Introductionmentioning
confidence: 99%
“…The geometrical description of the Millennium 120 MLC is done according to the blueprints of the collimator. By following this approach and conducting an accurate transport of radiation through all the collimating and beam-modifying elements of the gantry, it is possible to reproduce the dose distributions conformed by the linac without resorting to non-physical parameters such as the dynamic leaf gap ( 26 , 30 , 31 ). The geometrical description of the MLC is a faithful model of the actual collimator.…”
Section: Methodsmentioning
confidence: 99%